Nurses’ knowledge towards severe acute malnutrition management protocol and its associated factors - Abdu Oumer (International Journal of Public Health Science (IJPHS), 2019)
For appropriate management of severe acute malnutrition skilled, knowledgeable and concerned health professionals are critical for child survival. Thus assessing the knowledge of nurses towards management protocol of severe acute malnutrition is crucial step for targeted interventions. This study aimed to assess Knowledge towards Severe Acute Malnutrition Management Protocol and its Associated Factors among Nurses working in Hiwot Fana Specialized University Hospital, 2018. Cross-sectional study was conducted among eligible 132 nurses. Data were collected using self-administered questionnaire prepared from the national SAM management guideline of Ethiopia. SPSS version 20.0 software using frequency, tables, graphs, percentages and mean was used. Student t test and analysis of variance with F statistics and P value was computed. Overall, 65 (49.2%) of nurses had poor knowledge on SAM management. More than half, 100 (75.8%) of the nurses had experience in SAM management previously. Males were more likely to be knowledgeable (AOR=1.27) as compared to females. Nurses with the previous experience of managing malnourished child had 1.70) times more likely to be knowledgeable as compared to their counterparts. Having SAM training was associated with having higher knowledge score (AOR=1.56). Having SAM training was found to have significantly higher knowledge score (p=0.034). Knowledge level of nurses towards SAM management is not satisfactory. Those who ever involved in SAM management, having recent malnutrition training and gender were predictors of high knowledge score. There should be regular capacity building schemes for nurses especially for those who are involved in management of SAM at emergency or SAM unit.